2021
DOI: 10.3390/atmos12111402
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Particle Transport and Deposition in Upper and Lower Airways of Infant, Child and Adult Human Lungs

Abstract: Understanding transportation and deposition (TD) of aerosol particles in the human respiratory system can help clinical treatment of lung diseases using medicines. The lung airway diameters and the breathing capacity of human lungs normally increase with age until the age of 30. Many studies have analyzed the particle TD in the human lung airways. However, the knowledge of the nanoparticle TD in airways of infants and children with varying inhalation flow rates is still limited in the literature. This study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…PM 2.5 is injected from the mouth–throat surface of the model at the 60 L/min flow rate. The inlet velocity and outlet outflow conditions are used as boundary conditions [ 45 ]. In addition, the conditions of stationary walls and no-slip are applied to the airway walls.…”
Section: Resultsmentioning
confidence: 99%
“…PM 2.5 is injected from the mouth–throat surface of the model at the 60 L/min flow rate. The inlet velocity and outlet outflow conditions are used as boundary conditions [ 45 ]. In addition, the conditions of stationary walls and no-slip are applied to the airway walls.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a second-order implicit scheme is used to solve the numerical equations. A constant inlet velocity and zero-gauged pressure outlet boundary conditions have been applied for each lung model. , The required inlet air velocity during the inhalation phase is calculated based on the diameter of the inlet surface of G3. For the turbulence, the specification method used is intensity and viscosity ratio with values of turbulent intensity and turbulent viscosity ratio of 5% and 10, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the model considered here extends up to the fourth generation, and morphing allows controlling up to the third. Several studies have shown that drug deposition also occurs in subsequent generations, especially when considering diameters on the order of a few nanometers [68]. Time-variant inlet profiles could be applied and combined with the parametric model to reproduce the oscillatory respiratory flow [69,70].…”
Section: Limitations and Future Workmentioning
confidence: 99%